2002
DOI: 10.1890/0012-9658(2002)083[3369:lvipos]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal Variation in Palatability of Salt-Marsh Plants: Which Traits Are Responsible?

Abstract: Biogeographic theory predicts that intense consumer–prey interactions at low latitudes should select for increased defenses of prey relative to high latitudes. In salt marshes on the Atlantic coast of the United States, a community‐wide pattern exists in which 10 species of low‐latitude plants are less palatable to a diverse suite of herbivores than are high‐latitude conspecifics. Examination of proximate plant traits (toughness, palatability of polar and nonpolar extracts, nitrogen content) of high‐ and low‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
100
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 43 publications
(50 reference statements)
11
100
7
Order By: Relevance
“…We have a good understanding of how the importance of top-down and bottom-up factors changes at small spatial scales to affect ecological processes at a number of sites (Hacker andBertness 1995, Denno et al 2005). We also have an emerging understanding of latitudinal variation in herbivore population dynamics (Denno et al 1996) and plant-herbivore interactions (Siska et al 2002, Pennings et al 2009) at large geographic scales. Here we report on experimental work examining latitudinal variation in top-down and bottom-up processes that control populations of herbivores associated with the high-marsh shrub Iva frutescens.…”
Section: Introductionmentioning
confidence: 99%
“…We have a good understanding of how the importance of top-down and bottom-up factors changes at small spatial scales to affect ecological processes at a number of sites (Hacker andBertness 1995, Denno et al 2005). We also have an emerging understanding of latitudinal variation in herbivore population dynamics (Denno et al 1996) and plant-herbivore interactions (Siska et al 2002, Pennings et al 2009) at large geographic scales. Here we report on experimental work examining latitudinal variation in top-down and bottom-up processes that control populations of herbivores associated with the high-marsh shrub Iva frutescens.…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of latitude were not as dramatic as that of fertilizer addition, low-latitude plants were consistently larger, but lower in nitrogen, at the end of the experiment. Although high-latitude plants are higher in nitrogen, lower in phenolics and more palatable than low-latitude plants (Pennings, Siska & Bertness 2001;Siska et al 2002;Salgado & Pennings 2005), and although these differences are sufficient to cause geographic variation in herbivore body size (Ho, Pennings & Carefoot 2010), they were nevertheless overwhelmed in our experiments by fertilizer-induced nutritional status and food web composition. These findings are similar to those in our previous work with the high-marsh shrub Iva frutescens (Marczak et al 2011), where we found that latitudinal variation in plant quality had much smaller effects on herbivore Table 3.…”
Section: O C a L N O T G E O G R A P H I C S O U R C E S O F B mentioning
confidence: 76%
“…Moreover, the concentration of phenolics in Spartina is lower in plants from high (2.45 AE 0.13% dry mass) vs. low (3.16 AE 0.10%) latitudes (Siska et al 2002). Preference tests in the laboratory using a variety of herbivores demonstrated that both polar extracts (polar extracts containing allelochemicals in artificial diet) and live leaf tissue from high-latitude Spartina are far more palatable (more diet or leaf area consumed) than their low-latitude counterparts (Pennings, Siska & Bertness 2001;Siska et al 2002;Salgado & Pennings 2005). In sum, high-latitude plants in these marshes are known to be more nutritious, softer, less defended and more palatable than low-latitude plants.…”
Section: T H E S P a R T I N A F O O D W E Bmentioning
confidence: 90%
See 2 more Smart Citations